Vague Language in Online Medical Consultation - Linwei He; Eline Smit (University of Zurich, IKMZ - Department of Communication and Media Research, 2021)
Online medical consultation has become increasingly popular, while little is known about what features of such service can impact users' emotions and behaviours. This study looked into the language features of online text-based medical consultation. Specifically, the aim of this paper was to examine the effects of vague language (i.e., non-specific, imprecise language) on health-related uncertainty, and its affective and behavioural consequences, while considering individual differences in regulatory focus. A between-subject (vague language vs. precise language vs. control condition) web-based experiment was conducted (N = 249), where participants in the experimental groups read virtual doctor-patient conversations where the doctor used either vague or precise language. Results showed that vague language induced more uncertainty than precise language (p = .010); such uncertainty was appraised as a danger (r = .18, p = .004) but not an opportunity (r = .01, p = .932), and subsequently led to negative emotions (r = .45, p < .001). No effects were found on behavioural outcomes, and there was no moderation from regulatory focus. The results suggest that online healthcare providers should refrain from using vague language in communication with patients to avoid eliciting uncertainty and subsequent negative feelings. Future research is needed to further examine the behavioural effects of uncertainty and explore factors that could foster the appraisal of opportunity.